2015
DOI: 10.18697/ajfand.69.12390
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and nutrient intakes of a South African population and asymptomatic people infected with human immunodeficiency virus: The transition health and urbanisation in South Africa (THUSA) study.

Abstract: There is increased emphasis on the quality of food and the overall pattern of micronutrient intake as an integral consideration for food security particularly among people living with HIV/AIDS (PLWHA). However, limited data exist on food consumption and nutrient intakes for populations in sub-Saharan Africa. The study examined dietary patterns and their relationship with nutrient intakes in HIV uninfected (HIV-) and infected (HIV+) adults in North-West Province, South Africa. In this cross-sectional study, die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Three dietary patterns-animal-based, plant-based, and grainbased-were discovered in another study conducted in Malawi among pregnant HIV-positive women (Ramlal et al, 2015). Four dietary patterns-animal-based, staple-based, recommended diet, egg and breakfast cereals, legumes, and vegetables-were also discovered in a second study on the HIV-infected population in South Africa (Annan et al, 2015). A study on Danish women also identified three categories of food habits: western, intermediate, and healthconscious patterns (Knudsen et al, 2008).…”
Section: Discussionmentioning
confidence: 89%
“…Three dietary patterns-animal-based, plant-based, and grainbased-were discovered in another study conducted in Malawi among pregnant HIV-positive women (Ramlal et al, 2015). Four dietary patterns-animal-based, staple-based, recommended diet, egg and breakfast cereals, legumes, and vegetables-were also discovered in a second study on the HIV-infected population in South Africa (Annan et al, 2015). A study on Danish women also identified three categories of food habits: western, intermediate, and healthconscious patterns (Knudsen et al, 2008).…”
Section: Discussionmentioning
confidence: 89%
“…Annan et al’s 36 study showed a strong association between animal-based dietary patterns and micronutrient intake in HIV individuals. These studies suggested that inadequate nutritional intake (reduced or increased food intake) impacts the immune system, which is of substantial importance among HIV-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] The principal reason is overall vitamin D deficiencies in HIV-infected patients and the Iranian population in general. 16,36,47,48 Furthermore, there are many non-HIV-related risk factors for Vitamin D deficiency, including sex, advanced age, limited sunlight exposure, low levels of dietary Vitamin D intake, gastrointestinal absorption disorders, hepatic and renal diseases, higher body mass index, diabetes mellitus, and alcohol consumption. 42,43 We found no significant correlation between education level, marital status, employment status, smoking, medication usage, physical activity levels, depression history, disease duration, economic condition, participants' average energy and protein intake, and CD4 cell count.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations